Efeito de extratos de própolis verde e geoprópolis de abelha Canudo (Scaptotrigona sp.) e Jandaíra (Melipona subnitida) na resposta inflamatória e viabilidade de transplantes cutâneos alogênicos e autólogos - Brito, Parmênedes Dias de (Universidade Federal Rural do Semi-Árido, 2020)
Propolis and geopropolis are resinous products elaborated starting from exudates, oils and picked resins of plants by the bees. Those products are known for they present biological effects and they are used for popular due to the medicinal properties, besides in the treatment of wounds. The aim of this work was to evaluate the effect of the hydroalcoholic extract of green propolis (HEP), canudo bee geopropolis (Scaptotrigona sp.) (HEG-Can) And the geopropolis of bee jandaíra (Melipona subnitida) (HEG-Jan) on acute inflammation, chronic inflammation, cicatrization of wounds and autogenic and allogenic skin flaps. 36 healthy adult wistar rats, of both sexes, were distributed in five groups: treated animals with formulation containing 20% of; agreements with 20% of HEG-Can; agreements with 20% of HEG-Jan; group positive control (CG+) with pharmaceutical products registered as a positive control group (CG +); only vehicle as a negative control (CG-). Previously the analyses in vivo, was made a physical-chemical analysis for preliminary characterization of the extracts. The acute inflammation was induced by 1% carrageenan, chronic inflammation caused by a foreign body (circular sight glass) and wound healing was accompanied starting from wound circular of 8mm of diameter. Transplants were made with the incision and reallocation of two grafts cutaneous squares (1cm2), first to autograft and second to allograft, respectively. On the flavonoides content, the HEG-Jan group has a large amount (p<0.05), an intermediate amount of HEP and a lower amount of HEG-Can. HEP presented a pronounced effect on the acute inflammation (anti-edematous effect), moderate effect of the HEP-Can and HEG-Jan groups was registered. In chronic inflammation, the group HEG-Jan accelerated the process of formation of the granuloma when compared to the other extracts (HEP and HEPCan). In healing wounds, there was acceleration of the cicatrization due to effect of the extracts of HEP and HEP-Can in 16 days. The extracts show the protection of the skin graft area and discreet retard in the graft rejection (necrosis) of the autografts. In a similar way, however fewer accentuated it happened with the allografts. The several chemical classes of the geopropolis were probably responsible for the satisfactory acting in the analyses. Possibly the effects are biologically related to the presence of substances specific active. Besides, it is probable that the protecting effect against infections opportunists has collaborated with the sastisfatory results. The hydroalcoholic extracts of propolis from geopropolis have positive effects on the inflammatory processes and I repair of wound, as well as they promoted protection of the graft and retard in the graft rejection
Keywords: Autoenxerto; Aloenxerto; Granuloma; Abelha sem ferrão; Apis mellifera; Autograf; Allograft; Granuloma; Stingless bee; Apis mellifera; CIENCIAS AGRARIAS::MEDICINA VETERINARIA